Granulosa cell transcription is similarly impacted by superovulation and aging and predicts early embryonic trajectories - Daugėlaitė, Klaudija; Lacour, Perrine; Winkler, Ivana; Koch, Marie-Luise; Schneider, Anja; Schneider, Nina; Coraggio, Francesca; Tolkachov, Alexander; Nguyen, Xuan Phuoc; Vilkaite, Adriana; Rehnitz, Julia; Odom, Duncan T.; et al. (Nature Communications, 2025)
In vitro fertilization efficiency is limited in part because a fraction of retrieved oocytes fails to fertilize. Accurately evaluating their quality could significantly improve in vitro fertilization efficiency, which would require better understanding how their maturation may be disrupted. Here, we quantitatively investigate the interplay between superovulation and aging in mouse oocytes and their paired granulosa cells using a newly adapted experimental methodology. We test the hypothesis that superovulation disrupts oocyte maturation, revealing the key intercellular communication pathways dysregulated at the transcriptional level by forced hormonal stimulation. We further demonstrate that granulosa cell transcriptional markers can prospectively predict an associated oocyte’s early developmental potential. By using naturally ovulated old mice as a non-stimulated reference, we show that aging and superovulation dysregulate similar genes and interact with each other. By comparing mice and human transcriptional responses of granulosa cells, we find that age-related dysregulation of hormonal responses and cell cycle pathways are shared, though substantial divergence exists in other pathways.